AI-assisted problem-based learning: Effects on problem-solving abilities across learning styles - Rusman Zaenal Abidin; Maman Fathurrohman; Aan Hendrayana; Zahid Zufar At Thaariq (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
This study investigated the effect of Problem-Based Learning (PBL) assisted by Artificial Intelligence (AI) on students' problem-solving skills, with particular consideration for students' initial abilities and learning styles. The study employed a quasi-experimental design involving 120 undergraduate students, allocated into experimental and control groups. The results show that AI-assisted PBL greatly improves problem-solving skills (F=45.23, p<0.001, η²=0.38), but the effects varied, depending on the person's initial skill levels and learning styles. Students with low initial ability exhibited the most significant improvement (d=1.24), whereas visual learners derived the greatest benefit from AI-enhanced visualisations. These findings concluded that AI-assisted problem-based learning (PBL) can be an adaptive instructional strategy that addresses individual learning differences, with ramifications for creating more inclusive and customised educational interventions that mitigate achievement gaps and consider varied learning preferences in higher education settings.